Montreal's Square Mile: the making and transformation of a colonial metropole - Anastakis, Dimitry; Kirkland, Elizabeth; Nerbas, Don (University of Toronto Press, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

La Halte de La Visitation - Goulet, Patrick (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: La Visitation (église); Patrimoine; Sault-au-Récollet

Proprety and Power: Connecting the Dots - Olson, Sherry (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-23-00
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

La British and Canadian School de Montréal - MacLeod, Roderick; Poutanen, Mary Anne (Atlas historique du Québec. L'école au Québec, 2023)

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)

Marion Nelson Crawford, la partenaire du notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Number: 1
Keywords: Crawford; Alexander

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n27 Translators: _:n62469
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
issued: 2022-21-00
Keywords: Saint-Jean-Baptiste (village); Villages

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n95 Translators: _:n62402
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Montréal, Hospitable Capital City - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n139 Translators: _:n62391
Keywords: Hôtellerie; Marchés

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)

Going Together Like a Horse and Carriage: Rentier Marriages and Property Accumulation in Montréal, 1825-1903 - Sweeney, Robert C. H. (Histoire sociale / Social History, 2021)
Number: 112
Keywords: Famille; Logement; Mariage

Alexander Crawford, le notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 1
Keywords: Crawford; Alexander

Le marché Sainte-Anne et ses eaux souterraines. Imaginer et construire de façon innovatrice - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Sainte-Anne (marché)

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 2
Keywords: Famille; Logement; Quartiers; Rosemont

Louis-Joseph Papineau’s Seigneurialism, Republicanism, and Jeffersonian Inclinations - Guimond, Olivier (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
Number: 1
Keywords: Idéologies; Papineau; Louis-Joseph; Rébellions; Seigneurie

1844-1849. Montréal, nouveau siège du gouvernement - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Montréal, capitale accueillante - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Hôtellerie; Marchés

1840-1912: De la montée du Sault à la rue Lajeunesse: sept décennies de chemins de barrières... et quelques incendies - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 6
Keywords: Incendies; Routes; Rues

Carrières et pierre grise (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-22-00
Keywords: Carrière; De Lorimier (village); Géographie physique; Géologie; Histoire naturelle; Parcs; Plateau Mont-Royal; Quartiers; Travail; Villages; Églises

LAURIN, JAMES - Auger, Jean-François (Dictionnaire biographique du Canada, 2019)

La petite histoire, des origines jusqu'à 1925. Des carrières sous le parc Laurier - Côté, Julie; Cudia, Caroline (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-22-00
Keywords: Carrière; Parcs; Travail

MIGNAULT, ARTHUR - Litalien, Michel (Dictionnaire biographique du Canada, 2019)

Montreal Property-Owners of the 1850s: "Born or to Be Born" - Olson, Sherry (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Reporter: L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles
Keywords: Droit; Enfants; Famille; Logement

CURRY, NATHANIEL - Sutherland, David A. (Dictionnaire biographique du Canada, 2019)

" Je me souviens " d’un domaine seigneurial à Ahuntsic - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Number: 4
Keywords: Ahuntsic; Communautés religieuses; Domaine Saint-Sulpice; Logement; Seigneurie; Sulpiciens

The Modern City: 1840-1890 - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

The years of dispersion - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Denis-Benjamin Viger (1774-1861). Patriote assagi par la richesse sans en être aveuglé - Lavallée, Martin (Montréal en tête, 2018)
issued: 2018-23-00
Keywords: Foretier; Pierre; Seigneurie; Testaments; Viger; Denis-Benjamin

Mount Royal: The Top of the Island - MacLeod, Roderick (Montreal: The History of A North American City, 2018)
Keywords: Mont Royal; Mont-Royal (parc); Parcs

La grève générale des charpentiers-menuisiers de Montréal, 1833–1834 : réévaluation d’un acte fondateur autour du concept de légitimité - Tremblay, Robert (Labour / Le travail, 2018)
Keywords: Charpentiers; Grèves; Libéralisme; Maçons; Menuisiers

La Montreal Investment Association, le Montreal Investment Trust et la seigneurie de Beauharnois (1866–1941) - LaRose, André (Canadian Historical Review, 2017)
Number: 1
Keywords: Fiducie

L'architecture du Plateau Mont-Royal (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2017)
issued: 2017-23-00
Keywords: Carmélites; Communautés religieuses; Logement; Plateau Mont-Royal; Quartiers; Églises

Seigneur absent, seigneur effacé? Louis-Joseph Papineau et la gestion de la Petite-Nation par l’entremise de Denis-Benjamin, son frère et agent seigneurial (1817-1854) - Guimond, Olivier (Histoire Québec, 2016)
Number: 2
Keywords: Papineau; Louis-Joseph; Seigneurie

Le père du célèbre Louis-Joseph Papineau: Joseph Papineau, premier en tout - Aubin, Georges (Montréal en tête, 2015)
issued: 2015-23-00
Keywords: Arpenteurs; Notaires

Seigneurs and Landowners: An Ecclesiastical Economic Vision - Dickinson, John A. (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Translators: _:n46695
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Une plongée vertigineuse dans l'histoire sociale de l'île de Montréal. Autour de la maison Brignon-Lapierre - Lapierre, Michel (Montréal en tête, 2013)
Number: 64
Keywords: Brignon-Lapierre (famille); Rébellions

La ville moderne, 1840-1890 - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

Les années de dispersion - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Les différents propriétaires et leur histoire (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 2
Keywords: Chapman; Joseph; Congrégation de Notre-Dame; Crawford; John; Dupuy; Zacharie; Greater Montreal Land Company; Logement; Nivard de Saint-Dizier; Marie-Anne; Nivard de Saint-Dizier; Étienne; Nivard-De-Saint-Dizier (maison); Steward Hunter; William; Verdun

Le pont du domaine Saint-Gabriel - Douaire, Gilles (Histoire Québec, 2011)
Number: 3
Keywords: Communautés religieuses; Lachine (canal); Ponts; Saint-Gabriel (ferme); Seigneurie; Sulpiciens; Séminaire

City Streets as Environmental Grid: The Challenge of Private Uses and Municipal Stewardship - Olson, Sherry (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Rues

Propriétaires et promoteurs à LaSalle: plus d'un siècle d'évolution économique - Boucher, Bruno; Gravel, Denis (Éditions Histoire Québec, 2010)
Keywords: LaSalle; Logement

La petite histoire du moulin à eau de la rivière Saint-Pierre et de ses meuniers - Charlebois, Paul-Yvon (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Côtes; Meunerie; Sulpiciens

Reconstruire Montréal, rebâtir sa fortune - Dufaux, François; Olson, Sherry (Revue de Bibliothèque et Archives nationale du Québec, 2009)
Keywords: Faubourgs; Logement

Le légalisme à la sulpicienne - Savard, Rémi (Recherches amérindiennes au Québec, 2009)
Number: 1-2
Keywords: Autochtones; Communautés religieuses; Sulpiciens

Preservation of Westmount Homes built in the 1800s (The Westmount Historian, 2008)
Number: 1
Keywords: Conservation; Logement; Patrimoine; Quartiers; Westmount

WHA looks at some Prominent Westmounters (The Westmount Historian, 2008)
Number: 2
Keywords: Lait; Magasins; Port; Quartiers; Quincaillerie; Westmount

Le Vieux-Montréal: une toute autre histoire - Chartrand, Roger (Septentrion, 2007)
Keywords: Quartiers; Vieux-Montréal

Seigneurs et propriétaires: une logique ecclésiastique de l'économie - Dickinson, John A. (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Rapport sur la question du logement à Montréal; phase 1 - Roy, Christian (Laboratoire d'histoire et de patrimoine de Montréal, 2007)
issued: 2007-22-00
Keywords: Locataires; Logement; Pauvreté

A Gentleman of Substance: The Life and Legacy of John Redpath (1796-1869) - Feltoe, Richard (Dundurn Press, 2006)
Keywords: Hommes d'affaires; Redpath Sugar; Redpath; John; Sucre

Famille, affaires et succession, les enjeux de la gestion seigneuriale au Canada. Étude de la région montréalaise des 17e et 18e siècles - Couvrette, Sébastien (Histoire Québec, 2005)
Number: 3
Keywords: Famille; Seigneurie

Le logement traditionnel à Montréal et à Glasgow: partage et différence - Dufaux, François (Montreal-Glasgow, 2005)
Keywords: Logement

Une culture matérielle riche dans le « Red Light » de Montréal: Inventaire et fouille archéologiques au faubourg Saint-Laurent MTL03-25-3, MTL03-25-2 et BjFj-121, 2003: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2005)
Keywords: Faubourgs; Logement; Quartiers; Saint-Laurent (quartier)

Le régime seigneurial à Montréal - Beaudoin, Léo (Montréal en tête, 2004)
issued: 2004-23-00
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Risky Spaces : The Montreal Fire Insurance Company, 1817-20 - Sweeny, Robert C. H. (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Assurance; Incendies

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

La transmission du patrimoine seigneurial des familles du gouvernement de Montréal aux XVIIe et XVIIIe siècles - Couvrette, Sébastien (Université de Montréal, 2003)
Keywords: Famille; Notaires; Seigneurie

La maison Bagg: inventaire archéologique au site BiFj-32, 1992: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2003)
OCLC: 956636261
Keywords: Logement; Marchands

The Road to Terrace Bank: Land Capitalization, Public Space, and the Redpath Family Home, 1837-1861 - Macleod, Roderick (Journal of Canadian Historical Association / Revue de la Société historique du Canada, 2003)
Number: 1
Keywords: Redpath (famille); Redpath; John